The Evolution of Language: Towards Gestural Hypotheses - Zywiczynski, Przemyslaw (Dis/Continuities, 2019)
This book discusses the scope and development of the science of language evolution - a newly emergent field that investigates the origin of language. The book is addressed to audiences who are not professionally involved in science and presents the problems of language origins together with introductory information on such topics as the theory of evolution, elements of linguistic theory, the neural infrastructure of language or the signalling theory.